A Digital Global Map of Artificially Drained Agricultural Areas. - Feick, Sebastian; Siebert, Stefan; Döll, Petra (2005)
Artificial drainage of agricultural land, for example with ditches or drainage tubes, is used to avoid water logging and to manage high groundwater tables. Among other things it influences the nutrient balances by increasing leaching losses and by decreasing denitrification. To simulate terrestrial transport of nitrogen on a global scale, a digital global map of artificially drained agricultural areas was developed. The map depicts the percentage of each 5’ by 5’ grid cell that is equipped for artificial drainage. Information on artificial drainage in countries or sub-national units mainly derived by information from international data sets. Distribution to grid cells was based, for most countries, on the “Global Croplands Dataset” of Ramankutty et al. (1998) and the “Digital Global Map of Irrigation Areas” of Siebert et al. (2005). For some European countries CORINE land cover dataset was used instead of the both datasets mentioned above. Maps with outlines of artificially drained areas were available for 6 countries. The global drainage area on the map is 167 Mio hectares. For only 11 out of the 116 countries with information on artificial drainage areas, subnational information could be taken into account. Due to this coarse spatial resolution of the data sources, we recommended to use the map of artificially drained areas only for continental to global scale assessments. This documentation describes the dataset, the data sources and the map generation, and it discusses the data uncertainty.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IG.zentr.adigit
Keywords: data set; digital map; hydrology; artificial drainage